Social media addiction and its association with interpersonal communication skills among university students - Qasim Mohammed, Qahtan; Taha Ahmed Faraj (KHD-Production, 2026)
Social media addiction has become a significant mental health concern among university students, with studies indicating that approximately 30% to 40% of students exhibit signs of addiction. This phenomenon affects emotional well-being and social interaction. This study aims to assess the levels of social media addiction and communication skills (verbal, non-verbal, and written) among students at the University of Baghdad and explore their correlation, alongside sociodemographic variables. A quantitative, correlational study was conducted from November 22, 2024, to April 1, 2025. A convenient sample of 200 undergraduate students from four colleges was surveyed. Data collection tools included the Bergen Social Media Addiction Scale and the Communication Skills Scale, and data were analyzed using SPSS version 26.0. A moderate level of social media addiction was observed in 57% of students (M ± SD = 17.66 ± 4.965), and 92% exhibited moderate communication skills (M ± SD = 95.32 ± 11.118). The study found a weak positive correlation between social media addiction and communication skills (r = 0.18, p = 0.013). The mean social media addiction score was M = 17.66, with a standard deviation of SD = 4.97. While a slight positive correlation exists, sociodemographic factors did not significantly influence communication skills. Educational programs should consider strategies to improve both social media management and students' communication skills. The study recommended developing an intervention program to help students manage their social media use and implementing a training program to enhance communication skills across all student groups.